PENGEMBANGAN MEDIA PEMBELAJARAN PRAKTIKUM IPA BERBASIS BARANG BEKAS TOPIK TRANSPIRASI PADA TUMBUHAN MAHASISWA PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR (PGSD) FKIP UNIVERSITAS CENDERAWASIH. - Retno Hadisutjipto; BASA RUMAHORBO (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2018)
The research has been done for the development of learning tools practicum science based on secondhand goods to students of PGSD FKIP Cenderawsih University second semester 2017/2018. The purpose of this study is to find out how to design and develop learning tools of science practicum, to know the shortcomings and advantages of learning tools development science practicum based on secondhand of transpiration on plant the student of program study PGSD second semester 2017-2018 FKIP Cenderawasih University.The research sample is 31 studentsThe results in this study is to design a research development where the steps are as follows: observation, planning, data collection, making instrument, product design and produce product development in the form of practice guide. Before the practice guide is used, it is validated by 3 validation experts and in a limited-scale trial of 10 student of PGSD two generation of class 2017-2018 then in wide scale test to 31 students of PGSD study program at FKIP Cenderawasih University second semester 2017-2018, the benefit of learning tools of science practicum based on used goods is able out comes on the topic of transpiration on plants with n-Gain of 0,99 high category, the shortcomings of practicing lead-based practice manuals require considerable time to prepare practicum equipment and materials. The advantages of the use of secondhand goods in the development of learning tools laboratory science transpirations topics on plants is easily obtained, easy to get and taken anywhere without risk, can suppress waste disposal waste, train the creativity of lectures and students and improve student learning outcomes. Keywords: Practikum science & transpiration on plants